Intelligent security system based on face recognition and IoT. (2022) - Bagchi, Trinanjana; Mahapatra, Ankita; Yadav, Dipesh; Mishra, Daiwik; Pandey, Anish; Chandrasekhar, P.; Kumar, Ashwani
Abstract: Security is of utmost concern, whether it may be the security of data, assets and human life. With the development of technology, increasing use of IoT and biometrics authentication for security have gained popularity. Facial recognition is considered a universal, collectible, and accessible biometrics system. Biometric face recognition is based on the same identifier that humans use to distinguish one person from another. In this work, facial recognition has been considered to develop a highly reliable door lock system. Face-ID based security system has been developed using ESP32-CAM. The system performs real-time face detection and recognition, rapidly when a face is in front of camera. A prototype has been developed and tested, that evaluates the door lock system's working, efficiency, and reliability. The results show that it can be efficiently used to enhance human life and security and for commercial and residential purposes.